Untouched isolation enables targeted functional analysis of tumour‐cell‐derived extracellular vesicles from tumour tissues - Zi‐Li Yu; Xing‐Chi Liu; Min Wu; Shan Shi; Qiu‐Yun Fu; Jun Jia; Gang Chen (Journal of Extracellular Vesicles, 2022)
Abstract To accurately identify the functions of tumour‐cell‐derived extracellular vesicles (T‐EVs), EVs directly isolated from tumour tissues are much preferred over those derived from in vitro cultured tumour cell lines. However, the functional analysis of T‐EVs has still been severely limited by the difficulty in selective isolation of T‐EVs from tissue‐derived heterogeneous EVs, which also contain non‐tumour cell‐derived EVs. We here establish an untouched isolation strategy that specifically collects natural T‐EVs from tumour tissues by removing non‐tumour‐cell‐derived EVs. Different from traditional immunomagnetic separation, our isolation materials are directly bound to undesired non‐tumour‐cell‐derived EVs, preserving the natural properties of T‐EVs. Using this strategy, we reveal the distinct performances of tissue‐derived T‐EVs in organotropism to lymph nodes, immunosuppression and angiogenesis. The present work, which takes an extraordinary step forward in the isolation of EV subpopulation from tumour tissues, would dramatically accelerate the investigation of EV heterogeneity.